1998
DOI: 10.1103/physrevd.58.034012
|View full text |Cite
|
Sign up to set email alerts
|

Proton-proton spin correlations at charm threshold and quarkonium bound to nuclei

Abstract: The anomalous behavior of the spin-spin correlation at large momentum transfer in p p elastic scattering is described in terms of the degrees of freedom associated with the onset of the charm threshold. A non-perturbative analysis based on the symmetries of QCD is used to extract the relevant dynamics of the charmonium-proton interaction. The enhancement to p p amplitudes and their phase follow from analyticity and unitarity, giving a plausible explanation of the spin anomaly. The interaction between cc and li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
50
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 35 publications
11
50
0
Order By: Relevance
“…De Teramond and collaborators [14] have argued that reproducing the strength of the polarization asymmetry √ s in the vicinity of the threshold for cc production (about 10 GeV) requires an effective scattering length of about the same size as our result. We note that the estimate of Ref.…”
Section: −1supporting
confidence: 68%
See 1 more Smart Citation
“…De Teramond and collaborators [14] have argued that reproducing the strength of the polarization asymmetry √ s in the vicinity of the threshold for cc production (about 10 GeV) requires an effective scattering length of about the same size as our result. We note that the estimate of Ref.…”
Section: −1supporting
confidence: 68%
“…We note that the estimate of Ref. [14] includes the interactions of an ensemble of quarkonium states whose interactions with nucleons could be different than that of the J/ψ.…”
Section: −1mentioning
confidence: 99%
“…Furthermore, the large charm quark mass m c ≫ Λ QCD provides a natural renormalization point for which a perturbative QCD expansion is partly possible. In fact, studies have shown that the multi-gluon exchange between a cc pair and nucleons might induce a bound cc state with even light nuclei [14][15][16][17][18][19][20]. In such analysis, the low energy multi-gluon potential was modeled either from the effective theory obtained in the infinitely large m Q limit [16][17][18] or from extrapolating the high energy scattering via pomeron exchange to lower energy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our results for the mass shifts of the lowestcc states are surprisingly close to those reported in ref. [33][34][35][36].…”
Section: Heavy Quark System J/ψmentioning
confidence: 99%